A new species of Chiasmognathus from Iran, with a note on Chiasmognathus aegyptiacus in Israel (Hymenoptera: Apidae). - Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2008)
A new species of the rare cleptoparasitic bee genus Chiasmognathus Engel (Ammobatini) is described and figured from a female collected in northwestern Iran. Chiasmognathus rhagae sp. n. is generally similar to C. orientanus (Warncke) (Bulgaria, Turkey, Cyprus, Crete, and the Levant) or C. pashupati Engel (from southeastern Pakistan) but can be readily recognized by coloration and integumental sculpturing. In addition, a new locality in Israel is provided for C. aegyptiacus (Warncke). Keywords Anthophila, Apoidea, Asia, Middle East, Levant, Iran, taxonomy. Nomenclatural Acts rhagae Engel, 2008 (Chiasmognathus), spec. n.